Using visual vignettes to explore sensitive topics: a research note on exploring attitudes towards people with albinism in Tanzania. Issue 6 (1st November 2020) - Groot, Tjitske de; Jacquet, Wolfgang; Backer, Free De; Peters, Ruth; Meurs, Pieter
ABSTRACT: This study is one of the first to explore the use of (drawn) visual vignettes in qualitative research in Africa. The vignette method was used to discuss the sensitive topic of people's attitudes towards people with albinism in Tanzania among high school students. Focus was on two key questions: (i) To what extent was the vignette method implemented as intended?; (ii) Has the vignette method achieved its goal?. This research note discusses the effectivity of the visual vignette method as a tool to gain a better insight into people's attitudes towards people with albinism, but also describes the possibilities of visual vignettes as a tool for research on other sensitive topics.